Enhancement of SARS-CoV-2 receptor-binding domain activity by two microbial defensins - Gao, Bin; Zhu, Shunyi (Frontiers in Microbiology, 2023)
Peptide binders are of great interest to both basic and biomedical research due to their unique properties in manipulating protein functions in a precise spatial and temporal manner. The receptor-binding domain (RBD) of SARS-CoV-2 Spike protein is a ligand that captures human angiotensin-converting enzyme 2 (ACE2) to initiate infection. The development of binders of RBDs has value either as antiviral leads or as versatile tools to study the functional properties of RBDs dependent on their binding positions on the RBDs. Here we report two microbe-derived antibacterial defensins with RBD binding activity. These two naturally-occurring binders bind wild type RBD (WT RBD) and those from various variants with moderate to high affinity (7.6 – 1450 nM) and act as activators that enhance the ACE2-binding activity of RBDs. Using a computational approach, we mapped an allosteric pathway in WT RBD that connects its ACE2-binding sites to other distal region. The latter is targeted by the defensins, in which a cation-π interaction triggers the peptide-elicited allostery in RBDs. The discovery of the two positive allosteric peptides of SARS-CoV-2 RBD will promote the development of new molecular tools for investigating the biochemical mechanisms of RBD allostery.